Properties of irradiated sodium borosilicate glasses from experiment and atomistic simulations. Issue 9 (7th May 2021) - Sun, Mengli; Jahn, Sandro; Peng, Haibo; Zhang, Xiaoyang; Wang, Tieshan; Kowalski, Piotr M.
Abstract: With a combination of atomistic modeling and experimental techniques, we have investigated the structural and elastic parameters of sodium borosilicate glasses, including irradiation‐induced changes. Both approaches show that the Young's modulus depends linearly on the density of material. The simulated glass density and boron speciation match also the estimates by independent, elemental glass composition‐based models, indicating that atomistic simulations could be used in validation of theoretical models and experimental results. This allows us to formulate Young's modulus—density relationships for investigated borosilicate glasses and test the existing empirical model for description of Vickers hardness of these materials. The simulation of irradiation reveals a change of B [4] content under irradiation. By applying a simple defects accumulation procedure, we are able to correctly reproduce the measured critical irradiation dose of ~0.1 dpa and provide reasonable information on density change and stored internal energy. With the obtained agreements between the experimental and simulation results, we obtained superior insights into the atomic‐scale structural evolution of irradiated borosilicate glasses.